2020
DOI: 10.3389/fmicb.2020.590736
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Immunosensor for Detecting Perchlorate-Reducing Bacteria for Environmental Monitoring and Planetary Exploration

Abstract: Perchlorate anions are produced by chemical industries and are important contaminants in certain natural ecosystems. Perchlorate also occurs in some natural and uncontaminated environments such as the Atacama Desert, the high Arctic or the Antarctic Dry Valleys, and is especially abundant on the surface of Mars. As some bacterial strains are capable of using perchlorate as an electron acceptor under anaerobic conditions, their detection is relevant for environmental monitoring on Earth as well as for the searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…We validated the approach depicted above (Figure ) by screening several natural samples with a set of antibodies raised against ancestral resurrected proteins: one biofilm and three samples from different silica sinters from the El Tatio geyser field in Chile, one biofilm and one fumarole regolith sample from two hydrothermal areas in Iceland, one biofilm and two sediment samples from a hydrothermal field in New Zealand, one salt crust sample from a hypersaline perennial spring in the Canadian High Arctic, and one soil sample from a Mediterranean forest near Madrid (Spain; Table S1 and Figure S7). , Out of them, sample ET1 , from El Tatio geothermal field, showed positive immunodetection with anti-β-lactamase_PNCA and anti-Trx_LBCA antibodies (Figure ), the antibodies against the theoretically oldest proteins as inferred by ASR (Table ). Later, we demonstrated that analogues to peptides A and B were indeed present in the sample (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We validated the approach depicted above (Figure ) by screening several natural samples with a set of antibodies raised against ancestral resurrected proteins: one biofilm and three samples from different silica sinters from the El Tatio geyser field in Chile, one biofilm and one fumarole regolith sample from two hydrothermal areas in Iceland, one biofilm and two sediment samples from a hydrothermal field in New Zealand, one salt crust sample from a hypersaline perennial spring in the Canadian High Arctic, and one soil sample from a Mediterranean forest near Madrid (Spain; Table S1 and Figure S7). , Out of them, sample ET1 , from El Tatio geothermal field, showed positive immunodetection with anti-β-lactamase_PNCA and anti-Trx_LBCA antibodies (Figure ), the antibodies against the theoretically oldest proteins as inferred by ASR (Table ). Later, we demonstrated that analogues to peptides A and B were indeed present in the sample (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven natural samples were tested in this work, corresponding to different environments (hydrothermal, arctic, and mediterranean) and different types (silica precipitates, biofilm, salt crust, sediment, and soil). Most samples have been described elsewhere, , and their main features are gathered in Table S1. Crude liquid sample extracts to be analyzed by FSMI were prepared by ultrasonication and filtered (see SI, Experimental Section).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation